Comparing the recall of banner ad versus sponsored ad : Online - Namrata Shripad Keni (2008)
The objective of the study is to compare the two online advertising formats namely Banners and Sponsorships. Both the formats will be measured in their ability to affect cognitive or attitudinal exposure metrics and cognitive or attitudinal interactivity metrics.